2022
DOI: 10.3389/fmed.2022.834497
|View full text |Cite
|
Sign up to set email alerts
|

Superior gait performance and balance ability in Latin dancers

Abstract: BackgroundLatin dance consists of various fast and stability-challenging movements that require constant body adjustments to maintain proper posture and balance. Although human gaits are assumed to be symmetrical, several factors can contribute to asymmetrical behavior of the lower extremities in healthy adults. These include lower limb dominance, ground reaction forces, lower limb muscle power, foot placement angle, and range of joint motion. Gait impairment can lead to a high risk of falling, diminished mobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…The experiment was divided into three distinct parts to systematically assess various aspects of the participants' lower extremity biomechanics. (1) The participants engaged in a 10 min warm-up session, which involved jogging at a speed of 8 km/h. This warm-up not only prepared the participants physically but also allowed them to acclimatize and familiarize themselves with the experimental environment and become familiar with the experimental procedures.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The experiment was divided into three distinct parts to systematically assess various aspects of the participants' lower extremity biomechanics. (1) The participants engaged in a 10 min warm-up session, which involved jogging at a speed of 8 km/h. This warm-up not only prepared the participants physically but also allowed them to acclimatize and familiarize themselves with the experimental environment and become familiar with the experimental procedures.…”
Section: Methodsmentioning
confidence: 99%
“…With the evolution of Latin dance, an increasing number of scholars have taken interest in its significance. Research has revealed that Latin dance influences dancers' gait patterns and enhances their balance [1][2][3]. The achievement of good balance in dancers relies on the coordination of the somatosensory, visual, and vestibular systems [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, in recent years, more and more researchers have shifted their focus towards Latin dance. Some studies suggest that Latin dance can enhance body balance ( Kiliç and Nalbant, 2022 ; Liu et al, 2022 ), further highlighting its potential for rehabilitative interventions in individuals with Parkinson’s disease ( Hulbert et al, 2017 ; Ismail et al, 2021 ). Despite its benefits for balance improvement, the intricate movements involved in Latin dance also present a notable risk of ankle injuries.…”
Section: Introductionmentioning
confidence: 99%